Barbara Thiem, cello, Theresa Bogard, piano - Colorado State University. Department of Music, producers (managers) (Colorado State University. Libraries, 2014)
Date on program is incorrect, January 27, 2013 should be January 27, 2014.
CSU faculty: Barbara Thiem, cello, Theresa Bogard, piano
Virtuoso series
Keywords: CSU Faculty (Organ Recital Hall, 2014)